(untitled) (Confluenţe Bibliologice, 2014)
The author highlights the writer Angelo De Gubernatis merits. Angelo De Gubernatis was an Italian scholar, which left many written records about his relations with Romania. Angelo De Gubernatis is an example of loyalty in friendship and support Romanian case in Europe and it is worth stressing his enthusiasm for everything which is in connection with latinity reﬂected in any form: language, customs, songs, games, monuments.